Meningkatkan Daya Saing Produk Perbankan melalui Analisis Lingkungan Strategis: Kasus Produk Kredit Pegawai BPR Bhakti Daya Ekonomi - Kunto Ajibroto; Dematria Pringgabayu (Telaah Bisnis, 2017)
Abstract The purpose of this study is analyzing external factors and internal factors, so it will be possible to find out the most appropriate strategy formulation for BPR Bhakti Daya Ekonomi(BDE) in facing the increasingly fierce competition. The research method used is qualitative with data collection using interview and observation, while for data analysis using SWOT method which also use analysis of EFAS and IFAS. The results of this study indicate that the position of BPR BDE for Credit Employees products is located in quadrant IV. In this quadrant the bank is in a position where its internal advantage is relatively more dominant than its weakness. However, in facing of the environment, threat is relatively greater than the chances. This study recommend that BPR BDE should adopt a concentrated diversification strategy while still focusing on employee loans not only serving civil servants and TNI/POLRI, but adding new products that are credit products for private employees, which specifically target private employee markets, who already have a steady income.